The characteristics of narrow band imaging endoscopy in diagnosis of hypopharyngeal and laryngeal cancer and following-up post treatment - Thong, Le Chi; Thanh, Dang; Nam, Tran Phuong; Dung, Nguyen Quoc; Huy, Phan Ngo (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
ABSTRACT Background: This paper aimed to explore the characteristics of narrow band imaging (NBI) endoscopy in diagnosis of hypopharyngeal and laryngeal cancer and following – up post treatment Material and methods: A total of 75 patients included 36 patients with hypopharyngeal cancer and 39 patients with laryngeal cancer who had diagnosed at Department of Otolaryngology – Hue Central Hospital from 5/2017 to 7/2018. A descriptive study was conducted. Results: The age group 51 - 60 years occurred most often, 33.3%. The UICC stage III was 65.3%. Tumor was in ulcerative and infiltrate form (89.4%), edema and inflammation of margin tumor (41.3%), invasive (58.7%). Intrapapillary capillary loops (IPCL) type V-n was 46.7%. The tumor with IPCL type V-n had strong enhancement (51.3%) and moderate enhancement (44.4%) after contrast medium injection on CT scan. One month after treatment, there were 33,3% of tumor – free, 53.7% of mucosal edema and 13% tumor size-decreasing on NBI image. Conclusion: NBI endoscopy is a useful tool for diagnosing of hypopharyngeal and laryngeal cancer and following - up post treatment.